2011
DOI: 10.1152/ajpendo.00690.2010
|View full text |Cite
|
Sign up to set email alerts
|

Salt sensitivity in experimental thyroid disorders in rats

Abstract: This study assessed salt sensitivity, analyzing the effects of an increased saline intake on hemodynamic, morphological, and oxidative stress and renal variables in experimental thyroid disorders. Six groups of male Wistar rats were used: control, hypothyroid, hyperthyroid, and the same groups treated with salt (8% via food intake). Body weight, blood pressure (BP), and heart rate (HR) were recorded weekly for 6 wk. Finally, BP and HR were recorded directly, and morphological, metabolic, plasma, and renal vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 44 publications
2
20
1
Order By: Relevance
“…Our study clearly demonstrates that aging in female rats and a reduction in nephron number in male or female rats cause salt-sensitive hypertension. Moreover, variables related to salt-induced renal injury, such as proteinuria, N-acetyl-β-d-glucosaminidase, and isoprostanes, 16,29 were markedly increased by the high-salt intake in both UNX groups, indicating that UNX increases renal salt sensitivity.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Our study clearly demonstrates that aging in female rats and a reduction in nephron number in male or female rats cause salt-sensitive hypertension. Moreover, variables related to salt-induced renal injury, such as proteinuria, N-acetyl-β-d-glucosaminidase, and isoprostanes, 16,29 were markedly increased by the high-salt intake in both UNX groups, indicating that UNX increases renal salt sensitivity.…”
Section: Discussionmentioning
confidence: 90%
“…Our study clearly demonstrates that aging in female rats and a reduction in nephron number in male or female rats cause salt-sensitive hypertension. Moreover, variables related to salt-induced renal injury, such as proteinuria, N-acetyl-β-d-glucosaminidase, and isoprostanes, 16,29 were markedly increased by the high-salt intake in both UNX groups, indicating that UNX increases renal salt sensitivity.Several studies have extensively detailed morphological changes in the kidney during aging. 30,31 The normal aging process leads to slightly more pronounced changes in kidney morphology in male versus female rats.…”
mentioning
confidence: 90%
“…6 Our group recently observed that saline loading increased the ventricular weight (VW) and ventricular-to-body weight (VW/BW) ratio in control, hyperthyroid, and hypothyroid rats and increased the susceptibility of hyperthyroid rats to saline-induced cardiac hypertrophy. 2 The same study found that proteinuria levels were twofold higher in hyperthyroid rats than in controls and that a high salt intake did not change these levels in normal and hypothyroid rats but markedly increased them in hyperthyroid rats. Conversely, salt restriction has been reported to have beneficial effects on cardiac hypertrophy, proteinuria, and BP in normotensive and hypertensive rats.…”
Section: Introductionmentioning
confidence: 91%
“…2 Cardiac mass can be modulated by sodium concentrations in vitro or dietary sodium intake in vivo. In cultured neonatal rat myocardial myoblasts, cellular protein content and cell size increased with higher sodium concentration in the medium.…”
Section: Introductionmentioning
confidence: 99%
“…Damaged tubular cells release these enzymes into the ultrafiltrate, thereby increasing their activity in urine. Our group recently investigated urinary aminopeptidase activities as early biomarkers of kidney injury, finding that a higher activity of urinary aminopeptidases precedes the increase in proteinuria in hyperthyroid rats (Perez-Abud et al 2011). Moreover, from a diagnostic standpoint, urinary aminopeptidase values may be suitable predictors of renal injury.…”
Section: Renal Injury and Proteinuriamentioning
confidence: 99%